Peran adversity quotient terhadap work-life balance karyawan - Widad Syavirayana Shari; Tulus Winarsunu; Nandy Agustin Syakarofath (Cognicia, 2022)
The imbalance between the world of work and the personal life of employees can interfere with daily activities so that it can cause problems both in the world of work and in personal life. One of those who are considered capable of being able to better balance between personal and work life is the impulse in the individual to constantly move towards his life goals. Therefore, this study aims to test the role of the Adversity Quotient on the Work-Life Balance. A total of 150 employees actively participated in this study which was obtained using the Convenience Sampling technique. The instruments used are the Work/non-work Interference and Enhancement Scale and the Adversity Response Profile. The results of a simple linear regression test show that the Adversity Quotient is able to predict the Employee's Work-Life Balance. This means that the higher the Adversity Quotient, the higher the Work-Life Balance felt by employees. Keywords: adversity quotient, employee, work-life balance